The Effect of Financial Compensation on Employee Work Motivation at PT. Bumi Karsa in Makassar City - Peringga, Bayu; Amin, Abd Rahim; Arimbawa , I Gede Arya Pering; Ardhi Goeliling; Muhammad, A Fadel (PT. Maju Malaqbi Makkarana, 2023)
This study aims to determine and analyze employee work motivation at PT Bumi Karsa Makassar In connection with this, how employees can work as well as possible and employees have high motivation in completing work with the provision of compensation. So against this, this study aims to show the significance of the effect of compensation on employee work motivation. The population in this study were all employees of PT Bumi Karsa Makassar who received compensation in the form of salary, bonuses, and health benefits, totaling 60 people. The number of samples used was 60 people using saturated sampling theory. Data collection was carried out using questionnaire and documentation methods. The data analysis technique used is multiple linear regression analysis using Statistical Product and Service Solution (SPSS). The multiple linear regression equation produces the equation Y = 0.165 + 0.032X1 + 0.961X2. The results of this study found that compensation variables (financial and non-financial compensation) simultaneously affect work motivation and the F-Count value (4566,330) > F-Table (3.16). The results of the correlation analysis of determination (R Square) of 0.994 which shows that the compensation variable is able to contribute 99.4%. 0.6% is influenced by other variables not examined. The most dominant variable affecting motivation is the non-financial compensation variable among the two compensation variables with a t-count value (48.056) > t-table (1.672). While the financial compensation variable is influential but not significant with a t-count value (1.205) < t-table (1.672).